Clinical hypnosis, mindfulness and spirituality in palliative care - Casula, Consuelo (Annals of Palliative Medicine, 2017)
In this article, I do not intend to present the many and well-known treatments for relieving pain and distress symptoms of the physical body, damaged by terminal diseases, such as cancer, AIDS, multiple sclerosis. In this article, I’d rather focus my attention on clinical hypnosis for subjects who, freed from physical pain, thanks to palliative care, are open to receiving comfort and support for their psychological and spiritual suffering. The intent of this article is to express how clinical hypnosis can harmoniously integrate psychological and spiritual aspects so that the terminal patient can make peace with his/her past, with the people who have hurt him/her, and with the people who will suffer because of his/her death. This article will present some hypnotic suggestions inspired by universal wisdom of the Stoics, by positive psychology of Mindfulness, by laws of nature regarding changes, differences and mysteries. The basic assumption of the suggestions presented is that, if disease is an enemy to fight, death is an inevitable part of life: it cannot be avoided, or postponed or exchanged with anybody. It arrives when we have finished living. When death is preceded by an incurable disease, palliative care can offer a mantle of compassion and acceptance of what cannot be avoided. The words palliative comes from the Latin pallium—mantle. This article also presents some suggestions I have utilized several times with my patients. These suggestions have demonstrated their efficacy in alleviating patients’ suffering in coping with their disease and in facing death.